Remote control : new media, new ethics - Lumby, Catharine (Cambridge University Press, 2003)
This book examines the ethical challenges posed by new media formats, technologies and audiences. It considers how these genres and technologies work, how they are reshaping the public sphere, and how the connections between product and viewer, and producer and media consumer, are being changed by new shows and formats.